The relationship between quality factors, satisfaction, actual use and benefits of virtual programs for UAE youth - Alhammadi, Khulood Abdulbaset (2023)
Recognizing the importance of positive development among youth for the future economic growth and wellbeing of a nation, governments all over the world have made efforts to provide a variety of youth programs so that the youth can contribute positively and become the assets of the country. Although here have been extensive studies on the quality of youth development programs, the majority of these studies have focused on evaluating the effectiveness of developing youth’s positive growth. A study that investigates factors for the sustainability of the program is still lacking. Further, these studies focus on evaluating the youth programs in the developed rather than the developing countries. In addition, the newly transition on the mode of delivery from face-to-face to virtual youth programs has resulting in the need to examine the quality of the virtual youth programs. Although virtual learning (e-learning) has been extensively studied in the domain of formal education, studies of the quality of virtual learning adopted in the youth development programs organized by the government are still very limited. Therefore, the purpose of this study is to investigate the quality factors that influence satisfaction, actual use and benefits of virtual youth programs. This study investigated the virtual youth programs organised by the UAE government for their youth. It is motivated by the recent move of the UAE government to convert the face-to-face onsite youth programs to virtual youth programs due to people’s mobility restrictions of the pandemic COVID-19. Hence, it is crucial to examine the quality of these programs to ensure their sustainability. 19 hypotheses, consisting of 13 hypotheses that tested the direct relationship and six hypotheses that tested the mediating role of satisfaction and actual use have been developed. This study adopted a questionnaire survey, and 394 data collected from participants of virtual youth development programs in the UAE were analysed using a two-stage structural equation modelling methodology. It was found that the three quality factors have significant positive relationship on satisfaction and two quality factors have significant positive relationship on actual use. The study also found that satisfaction fully mediates the relationship between information quality, user efficacy and actual use, while partially mediates the relationship between instructor quality and actual use. Meanwhile, the actual use partially mediates the relationship between satisfaction and benefits. As a conclusion, the quality factors that have impact on satisfaction may not necessarily have impact on actual use. Additionally, satisfaction has partial mediation effects on quality factors and actual use, while actual use has partial mediation effect on benefits. This study contributes to the knowledge of quality factors that influence satisfaction, actual use and benefits for sustainable implementation of virtual youth programs in the UAE, specifically and the Middle Eastern countries in general. It also provides valuable insights, specifically for the Ministry of Youth to plan strategically and design sustainable virtual youth programs with the aim of achieving the UAE Centennial 2071.